2021
DOI: 10.1177/23743735211018083
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Outpatient Clinics and Opinions of Telehealth by Caucasian and South Asian Patients’ With Celiac Disease

Abstract: Outpatient clinics are an important part of chronic disease management, including that of celiac disease. During the coronavirus disease 2019 (COVID-19) global pandemic, telephone and online video consultations with health care professionals have substantially increased. This study aimed to explore the experience and opinions of adults, with celiac disease, toward face-to-face clinic appointments and alternatives, such as telehealth. Semistructured qualitative interviews with 37 patients were undertaken (75% W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Satisfaction studies report the use of patient satisfaction questionnaires resulting in patient satisfaction scores [18,21,22,25] whereas "patient engagement" refers to the amount of engagement with eHealth solutions [30] or online patient engagement practices [31]. PX is also equated with the experiences of patients [20,[32][33][34][35][36], which is described as related to technology (e.g., "virtual experience for patients with COVID-19 symptoms" [33] and "telemedicine experiences of individuals" [34]). "Patient perception" refers to the "perception of the interaction related to use of a telemedicine service" [22] or to "patient perceptions of the virtual rounding experience" [32].…”
Section: How Has Px Been Defined?mentioning
confidence: 99%
See 3 more Smart Citations
“…Satisfaction studies report the use of patient satisfaction questionnaires resulting in patient satisfaction scores [18,21,22,25] whereas "patient engagement" refers to the amount of engagement with eHealth solutions [30] or online patient engagement practices [31]. PX is also equated with the experiences of patients [20,[32][33][34][35][36], which is described as related to technology (e.g., "virtual experience for patients with COVID-19 symptoms" [33] and "telemedicine experiences of individuals" [34]). "Patient perception" refers to the "perception of the interaction related to use of a telemedicine service" [22] or to "patient perceptions of the virtual rounding experience" [32].…”
Section: How Has Px Been Defined?mentioning
confidence: 99%
“…These studies point out the following quality aspects of remote care: patient burden [55], access to information [55], the amount of information given to the patient by the provider [56], the experience of being heard [56,57], trust towards the provider concerning care [56], the ease of contacting the clinic and scheduling the appointment [35,56,57], the experience of safety protection [35,57,58], and the decrease in nonverbal communication [36].…”
Section: Components Of Px Arising From the Ehealth Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…The importance of this issue is seen in that South Asians who did not understand food labelling had a significantly poorer dietary adherence than those who did [3]. Clearly, language barriers play a significant role in such difficulties, as demonstrated in a study of telephone clinics [4]. Indeed, a recent systematic review of 40 published studies has shown that significant barriers to compliance include: lower knowledge of coeliac disease (35%); restaurant/ supermarket shopping (30%); poor patient education from practitioner (17.5%); and low intention/motivation to adhere to a GFD (17.5%) [5].…”
Section: Introductionmentioning
confidence: 99%